Studi Pengaruh Variasi Konsentrasi Asam Posfat (H3PO4) dan Waktu Perendaman Karbon terhadap Karakteristik Karbon Aktif dari Kulit Durian - Husin, Amir; Hasibuan, Asmiah (Talenta Publisher (Universitas Sumatera Utara), 2020)
Durian shell is one of the agricultural wastes has the potency to valuable product Â therefore this study aims to utilize durian shells in activated carbon production and examine effect of variations phosphoric acid (H3PO4) concentration and carbon soaking time to characteristics of activated carbon. Durian shell pyrolyzed at 400oC for 2 hours, milled using ball mill, sifted with a 100 mesh sieve, and carbon is activated with soaking using phosphoric acid (H3PO4) with various concentrations of 30, 40, 50, 60 and 70% (v/v) and soaking time of 3 hours, 6 hours, 9 hours, 12 hours, and 15 hours. Effect of variation concentration and soaking time shows the characterization of activated carbon are fluctuating. Activated carbon with the highest iodine number of 1,080,1728 mg/g obtains at activator concentration 30% (v/v) for 9 hours. Results of the SEM-EDX analysis of activated carbon show that mesoporous group, BET analysis shows â€‹â€‹44,372 m2/g of surface area.